2000
DOI: 10.1093/ajcn/71.4.885
|View full text |Cite
|
Sign up to set email alerts
|

Thigh adipose tissue distribution is associated with insulin resistance in obesity and in type 2 diabetes mellitus

Abstract: SFAT and IMAT are markers of IR in obesity and DM although they are much smaller than SCAT, which does not predict IR. Muscle composition reflecting increased fat content is also associated with IR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

27
507
6
5

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 607 publications
(553 citation statements)
references
References 33 publications
27
507
6
5
Order By: Relevance
“…This could have lead to a systematic bias resulting in a lower estimate of muscle change when compared to CT. Previous investigations found that subfascial fat is more metabolically active than subcutaneous fat (Goodpaster et al, 2000b) and may be significantly affected by interventions such as exercise or weight loss (Goodpaster et al, 2000a). Finally, this difference could also be due to the ROI used.…”
Section: Discussionmentioning
confidence: 99%
“…This could have lead to a systematic bias resulting in a lower estimate of muscle change when compared to CT. Previous investigations found that subfascial fat is more metabolically active than subcutaneous fat (Goodpaster et al, 2000b) and may be significantly affected by interventions such as exercise or weight loss (Goodpaster et al, 2000a). Finally, this difference could also be due to the ROI used.…”
Section: Discussionmentioning
confidence: 99%
“…27 IMF is a better predictor of insulin resistance in nondisabled, obese diabetics and nondiabetics compared to subcutaneous and subfascial fat. 12 Moreover, IMF explains 70% of glucose intolerance after chronic SCI. 4 The mechanism relating IMF and insulin resistance is not clear; however, the release of intracellular fatty acid intermediates (eg, diacylglycerol, ceramide, long-chain acyl-CoA) from IMF could impair insulin signaling.…”
Section: Discussionmentioning
confidence: 99%
“…10 It has recently been determined that in complete SCI IMF accounts for a 70% reduction in glucose tolerance. 4 Goodpaster et al 12 showed also that IMF is negatively correlated with insulin sensitivity in obese and non-obese subjects with and without type II diabetes.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Intramuscular adipose tissue—here defined as clusters of adipocytes interspersed between skeletal muscle fibres—is generally associated with systemic insulin resistance,18, 19 decreased muscle strength20 and, in older adults, impaired mobility 21, 22, 2324.…”
Section: Introductionmentioning
confidence: 99%